Effect of salinity in heterotrophic nitrification/aerobic denitrification performed by acclimated microbiota from oil-produced water biological treatment system. (May 2018) - Silva, Lívia Carneiro Fidélis; Lima, Helena Santiago; Sartoratto, Adilson; Sousa, Maira Paula de; Torres, Ana Paula Rodrigues; Souza, Rodrigo Suhett de; de Paula, Sérgio Oliveira; Oliveira, Valéria Maia de; Silva, Cynthia Canêdo da
Abstract: Mixed cultures salt acclimated showed high efficiency in heterotrophic nitrification/aerobic denitrification process in hypersaline conditions. They were able to remove 80% of ammonium in Heterotrophic Nitrification Medium (HNM) with 12 and 14% of salt. Above these salinity, the process still had 40% ammonium removal up to 20% of salt. Chromatography analysis validated the occurrence of the heterotrophic nitrification/aerobic denitrification process in all studied salinities (6%–20% of NaCl). However, with increasing salinity, the N2 production was smaller and took longer than the unsalted control. Microbial diversity analysis of mixed cultures showed that different groups of nitrifying microorganisms were involved in ammonium removal, including heterotrophic nitrifying/aerobic denitrifying genera such as Pseudomonas, Paracoccus, Bacillus, Halomonas, Acinetobacter and Klebsiella . In addition, this analysis also revealed that the acclimation process allowed the adaptation of the microorganisms to high saline conditions and ammonium removal up to 20% of salt. This work showed that heterotrophic nitrification/aerobic denitrification process could occur in high salinity after microbiota acclimation step, and these mixed acclimated cultures have a potential for application in hypersaline effluent treatment. Highlights: All mixed cultures performed heterotrophic nitrification-aerobic denitrification. Mixed cultures removed 100% of ammonium with 6 and 8% of NaCl. Mixed cultures removed 80% of ammonium with 12 and 14% of NaCl. Acclimation process was effective to ammonium removal in high salinity. High potential application of mixed cultures for saline wastewater treatment.